Relatório Figueiredo e a Comissão Nacional da Verdade : a política indigenista no Estado de Goiás - Gomes Júnior, Alaor de Abreu (2020)
The present research aimed to critically analyze the nuances and characteristics of the national indigenous policy and its effects on certain indigenous ethnicities in the State of Goiás. The actions of the Brazilian Republican State in relation to the indigenous people were based on the state tutelage regime managed by a federal agency created especially for this purpose (Indian Protection Service and National Indian Foundation). Thus, the object of the work focuses on the application of this indigenous policy, in relation to two indigenous populations from Goiás, Avá-Canoeiro and Iny Karaja. The problem arose from the observation that, throughout the researched period, there was a continuation of the indigenous policy, characterizing a process of physical violations of these indigenous ethnic groups and intensification of interference in their territory. For the development of this work, a survey of the bibliographic debate on indigenous politics in the country and in Goiás was carried out. The research developed prioritized, in its analysis, two important documents: the Figueiredo Report (1967) and the Report of the National Truth Commission (2014), as both contain fundamental information about the way in which the indigenous policy was implemented in the country between the 1960s and 1980s.